Anti-crack concrete and preparation method thereof

By modifying the preparation of fine aggregates and fibers, and using retarders such as borax or boric acid in concrete, the problem of cracking in traditional concrete is solved, which significantly improves tensile strength and toughness, and delays the cement hydration speed. Achieve more efficient crack resistance.

CN119191790APending Publication Date: 2024-12-27HEFEI DONGKAI NEW BUILDING MATERIALS
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411339328.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional concrete is prone to cracks when loads or environmental changes, which affects the stability and durability of the structure. The existing crack resistance technology is costly and has limited effect.

Method used

Prepare by modifying the fine aggregate and fibers, and adding borax or boric acid to the concrete as a retarder, the crack resistance of the concrete is improved. The specific steps include soaking and drying the fine aggregate in the aqueous polyvinyl alcohol solution, soaking and drying the fibers in the polyacrylamide solution, combining high-performance polycarboxylic acid water reducing agent and polypropylene mesh fiber, adjusting the concrete ratio to enhance the Tensile strength and toughness.

Benefits of technology

It effectively improves the crack resistance of concrete, prevents cracks from occurring and expanding, significantly improves the tensile strength and toughness of concrete, delays the cement hydration speed, reduces the occurrence of early cracks, and significantly improves the crack resistance of concrete.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191790A_ABST
    Figure CN119191790A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of concrete, in particular to anti-crack concrete and a preparation method thereof.According to the anti-crack concrete, fine aggregate and fibers are subjected to modification preparation operation, and the fine aggregate is added into a polyvinyl alcohol aqueous solution to be soaked and dried, so that the cohesiveness and crack resistance of the fine aggregate can be effectively improved; the polypropylene reticular fibers are soaked and dried in a polyacrylamide solution, so that the tensile strength and toughness of the concrete can be effectively enhanced, cracks are prevented from being generated and expanded, concrete anti-cracking preparation based on a raw material level is realized, and the anti-cracking performance of the concrete is improved; by adding the borax or boric acid coagulant into the concrete raw materials, the cement hydration speed can be effectively delayed, hydration heat concentration can be reduced, heat in cement can be conveniently dissipated, early cracks of the concrete can be reduced, and the crack resistance of the concrete can be further improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to crack-resistant concrete, in particular to crack-resistant concrete and a preparation method thereof. Background Art

[0002] As a widely used building material, concrete has high compressive strength, can bear large loads, has good durability, can resist erosion by natural factors such as weathering and corrosion, prolongs the service life of buildings, and forms a whole after solidification, with a tight structure and not easy to separate and peel off. In recent years, with the continuous expansion of building scale and the continuous increase of structural height, the crack resistance of concrete structures has received more and more attention.

[0003] Traditional concrete has a certain degree of brittleness and is prone to cracks when affected by loads or environmental changes, affecting the stability and durability of the structure. Existing crack-resistant concrete technologies mainly include: adding crack control agents, adjusting concrete mix ratios, adding steel cages and other methods. However, these methods have the disadvantages of high cost and limited effect, and it is difficult to effectively solve the crack resistance problems encountered in actual engineering. Based on the above reasons, the present invention proposes a crack-resistant concrete and a preparation method thereof. Summary of the invention

[0004] In view of the deficiencies in the prior art, the present invention provides a crack-resistant concrete and a preparation method thereof.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0006] A crack-resistant concrete comprises the following raw materials in parts by weight: 140-200 parts of cement, 120-180 parts of fine aggregate, 220-320 parts of coarse aggregate, 5-10 parts of water reducer, 2-6 parts of fiber, 4-8 parts of retarder and 60-80 parts of water.

[0007] As a preferred technical solution of the present invention, the cement is silicate cement, and the grade of the cement is not less than 42.5.

[0008] As a preferred technical solution of the present invention, the fine aggregate is medium sand with a fineness modulus of 2.6-3.0, and the coarse aggregate is continuously graded crushed stone with a particle size of 5-25 mm.

[0009] As a preferred technical solution of the present invention, the water reducer is a high-performance polycarboxylate water reducer.

[0010] As a preferred technical solution of the present invention, the fiber is selected from polypropylene mesh fiber, the number average molecular weight of the polypropylene mesh fiber can be 3 million to 8 million, and the length of the polypropylene mesh fiber is 6 to 10 mm.

[0011] As a preferred technical solution of the present invention, the retarder is selected from one or both of borax and boric acid.

[0012] A method for preparing crack-resistant concrete comprises the following steps:

[0013] S1: performing modification and preparation operations on fine aggregate and fiber, and weighing specified weight portions of raw materials;

[0014] S2: Put the coarse aggregate and the fine aggregate into the mixer, and use the mixer to fully mix the coarse aggregate and the fine aggregate;

[0015] S3: adding cement to the fully mixed coarse aggregate and fine aggregate, and mixing and stirring again to fully mix the coarse aggregate, fine aggregate and cement;

[0016] S4: Add retarder, water reducer and water into a mixer according to the proportion and stir, and continuously add fiber during the stirring process to keep stirring;

[0017] S5: After mixing is completed, the concrete is discharged for pouring and curing.

[0018] As a preferred technical solution of the present invention, the modification preparation of fine aggregate in step S1 includes the following steps:

[0019] S11: preparing a polyvinyl alcohol aqueous solution with a concentration of 4% to 8%;

[0020] S12: placing fine aggregate into a designated container, and pouring polyvinyl alcohol aqueous solution into the container, ensuring that the polyvinyl alcohol aqueous solution fully immerses the fine aggregate;

[0021] S13: After soaking for 30 minutes, the fine aggregate is taken out and dried to complete the modification preparation of the fine aggregate.

[0022] As a preferred technical solution of the present invention, the modification preparation of the fiber in step S1 includes the following steps:

[0023] S21: weigh a certain amount of polyacrylamide solution and a specified amount of fiber;

[0024] S22: Adding the fiber into the polyacrylamide solution, and allowing the polyacrylamide solution and the fiber to be fully soaked;

[0025] S23: The soaked fibers are taken out and aired at 37-42 degrees Celsius for 1.5-2.5 hours to complete the modification of the fibers.

[0026] The embodiment of the present invention provides a crack-resistant concrete and a preparation method thereof, which has the following

[0027] Beneficial effects:

[0028] 1. The present invention performs modification and preparation operations on fine aggregate and fiber, and can effectively improve the bonding and crack resistance of fine aggregate by adding fine aggregate into polyvinyl alcohol aqueous solution for soaking and drying, and can effectively enhance the tensile strength and toughness of concrete by soaking polypropylene mesh fiber in polyacrylamide solution for drying, and prevent cracks from being generated and expanded, thereby realizing the crack resistance preparation of concrete based on the raw material level and improving the crack resistance of concrete;

[0029] 2. The present invention can effectively delay the cement hydration speed, reduce the hydration heat concentration, facilitate the heat dissipation in the cement, reduce early cracks in the concrete, and further improve the crack resistance of the concrete by adding borax or boric acid coagulant into the concrete raw materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the embodiments of the present invention, they are used to explain the present invention and do not constitute a limitation of the present invention. In the accompanying drawings:

[0031] Figure 1 It is the raw material composition table of the present invention;

[0032] Figure 2 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION

[0033] The preferred embodiments of the present invention are described below in conjunction with the accompanying drawings. It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0034] Embodiment 1: Figure 1-2 As shown, a crack-resistant concrete includes the following raw materials in parts by weight: 140 parts of cement, which is silicate cement with a grade of not less than 42.5, 120 parts of fine aggregate, which is medium sand with a fineness modulus of 2.6-3.0, 220 parts of coarse aggregate, wherein the coarse aggregate has a particle size of 5-25 mm and is continuously graded crushed stone, 5 parts of water reducer, which is a high-performance polycarboxylate water reducer, 2 parts of fiber, which is polypropylene mesh fiber, which has a number average molecular weight of 3 million to 8 million and a length of 6 to 10 mm, 4 parts of retarder, which is borax or boric acid or both, and 60 parts of water.

[0035] After observation and testing, no cracks were found on the concrete surface and the splitting tensile strength was 5.72MPa.

[0036] Embodiment 2: Figure 1-2As shown, a crack-resistant concrete includes the following raw materials in parts by weight: 200 parts of cement, which is silicate cement with a grade of not less than 42.5, 180 parts of fine aggregate, which is medium sand with a fineness modulus of 2.6-3.0, 320 parts of coarse aggregate, wherein the coarse aggregate has a particle size of 5-25 mm and is continuously graded crushed stone, 10 parts of a water reducer, which is a high-performance polycarboxylate water reducer, 6 parts of fiber, which is polypropylene mesh fiber, which has a number average molecular weight of 3 million to 8 million and a length of 6 to 10 mm, 8 parts of a retarder, which is one or all of borax or boric acid, and 80 parts of water.

[0037] After observation and testing, no cracks were found on the concrete surface and the splitting tensile strength was 6.62MPa.

[0038] Embodiment 3: Figure 1-2 As shown, a crack-resistant concrete includes the following raw materials in parts by weight: 170 parts of cement, which is silicate cement with a grade of not less than 42.5, 150 parts of fine aggregate, which is medium sand with a fineness modulus of 2.6-3.0, 270 parts of coarse aggregate, wherein the coarse aggregate has a particle size of 5-25 mm and is continuously graded crushed stone, 8 parts of water reducer, which is a high-performance polycarboxylate water reducer, 4 parts of fiber, which is polypropylene mesh fiber, which has a number average molecular weight of 3 million to 8 million and a length of 6 to 10 mm, 6 parts of retarder, which is borax or boric acid or both, and 70 parts of water.

[0039] After observation and testing, no cracks were found on the concrete surface and the splitting tensile strength was 7.59 MPa.

[0040] A method for preparing crack-resistant concrete comprises the following steps:

[0041] S1: performing modification and preparation operations on fine aggregate and fiber, and weighing specified weight portions of raw materials;

[0042] Specifically, the modification preparation of fine aggregate includes the following steps:

[0043] S11: preparing a polyvinyl alcohol aqueous solution with a concentration of 4% to 8%;

[0044] S12: placing fine aggregate into a designated container, and pouring polyvinyl alcohol aqueous solution into the container, ensuring that the polyvinyl alcohol aqueous solution fully immerses the fine aggregate;

[0045] S13: After soaking for 30 minutes, the fine aggregate is taken out and dried to complete the modification preparation of the fine aggregate.

[0046] Further, the modification and preparation of the fiber includes the following steps:

[0047] S21: weigh a certain amount of polyacrylamide solution and a specified amount of fiber;

[0048] S22: Adding the fiber into the polyacrylamide solution, and allowing the polyacrylamide solution and the fiber to be fully soaked;

[0049] S23: The soaked fibers are taken out and aired at 37-42 degrees Celsius for 1.5-2.5 hours to complete the modification of the fibers.

[0050] S2: Put the coarse aggregate and the fine aggregate into the mixer, and use the mixer to fully mix the coarse aggregate and the fine aggregate;

[0051] S3: adding cement to the fully mixed coarse aggregate and fine aggregate, and mixing and stirring again to fully mix the coarse aggregate, fine aggregate and cement;

[0052] S4: Add retarder, water reducer and water into a mixer according to the proportion and stir, and continuously add fiber during the stirring process to keep stirring;

[0053] S5: After the mixing is completed, the concrete is discharged for pouring and curing. The test sample is a standard cubic sample of 150 mm×150 mm×150 mm. There are 15 standard cubic samples in each embodiment.

[0054] In summary, the crack resistance of concrete can be effectively improved by modifying fine aggregate and fiber and adding retarders to the raw materials.

[0055] Finally, it should be noted that in the description of the present invention, it should be noted that the terms "vertical", "up", "down", "horizontal", etc. indicate orientations or positional relationships based on the orientations or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation. Therefore, they cannot be understood as limitations on the present invention.

[0056] In the description of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention is described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A crack-resistant concrete, characterized in that: The invention comprises the following raw materials in parts by weight: 140-200 parts of cement, 120-180 parts of fine aggregate, 220-320 parts of coarse aggregate, 5-10 parts of water reducer, 2-6 parts of fiber, 4-8 parts of retarder and 60-80 parts of water.

2. The crack-resistant concrete according to claim 1, characterized in that: The cement is silicate cement, and the grade of the cement is not less than 42.

5.

3. The crack-resistant concrete according to claim 1, characterized in that: The fine aggregate is medium sand with a fineness modulus of 2.6-3.0, and the coarse aggregate is continuously graded crushed stone with a particle size of 5-25 mm.

4. The crack-resistant concrete according to claim 1, characterized in that: The water reducing agent is a high performance polycarboxylate water reducing agent.

5. The crack-resistant concrete according to claim 1, characterized in that: The fiber is a polypropylene mesh fiber, the number average molecular weight of the polypropylene mesh fiber can be 3 million to 8 million, and the length of the polypropylene mesh fiber is 6 to 10 mm.

6. The crack-resistant concrete according to claim 1, characterized in that: The retarder is selected from one or both of borax and boric acid.

7. A method for preparing crack-resistant concrete according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: performing modification and preparation operations on fine aggregate and fiber, and weighing specified weight portions of raw materials; S2: Put the coarse aggregate and the fine aggregate into the mixer, and use the mixer to fully mix the coarse aggregate and the fine aggregate; S3: adding cement to the fully mixed coarse aggregate and fine aggregate, and mixing and stirring again to fully mix the coarse aggregate, fine aggregate and cement; S4: Add retarder, water reducer and water into a mixer according to the proportion and stir, and continuously add fiber during the stirring process to keep stirring; S5: After mixing is completed, the concrete is discharged for pouring and curing.

8. The method for preparing crack-resistant concrete according to claim 7, characterized in that: The modification preparation of fine aggregate in step S1 includes the following steps: S11: preparing a polyvinyl alcohol aqueous solution with a concentration of 4% to 8%; S12: placing fine aggregate into a designated container, and pouring polyvinyl alcohol aqueous solution into the container, ensuring that the polyvinyl alcohol aqueous solution fully immerses the fine aggregate; S13: After soaking for 30 minutes, the fine aggregate is taken out and dried to complete the modification preparation of the fine aggregate.

9. The method for preparing crack-resistant concrete according to claim 7, characterized in that: The modification preparation of the fiber in step S1 includes the following steps: S21: weigh a certain amount of polyacrylamide solution and a specified amount of fiber; S22: Adding the fiber into the polyacrylamide solution, and allowing the polyacrylamide solution and the fiber to be fully soaked; S23: The soaked fibers are taken out and aired at 37-42 degrees Celsius for 1.5-2.5 hours to complete the modification of the fibers.